2014
DOI: 10.1038/cddis.2014.212
|View full text |Cite
|
Sign up to set email alerts
|

Interconnections between autophagy and the coagulation cascade in hepatocellular carcinoma

Abstract: Autophagy has an important role in tumor biology of hepatocellular carcinoma (HCC). Recent studies demonstrated that tissue factor (TF) combined with coagulation factor VII (FVII) has a pathological role by activating a G-protein-coupled receptor called protease-activated receptor 2 (PAR2) for tumor growth. The present study aimed to investigate the interactions of autophagy and the coagulation cascade in HCC. Seventy HCC patients who underwent curative liver resection were recruited. Immunohistochemical stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…Spontaneous breast cancer development is delayed in both strains and to a similar extent in double‐deficient mice, indicating that PAR2 and downstream TF cytoplasmic domain phosphorylation cooperate in cancer progression, consistent with human pathology data in breast cancer . TF‐FVIIa‐PAR2 signaling has also been linked to human hepatocellular carcinoma (HCC) progression independent of downstream coagulation . In addition, TF ΔCT and PAR2‐deficient mice were similarly protected from carbon tetrachloride (CCl 4 ) damage leading to hepatic fibrosis involving transforming growth factor (TGF) β and macrophage activation.…”
Section: Tf‐par2 Signaling In Inflammatory Diseases and Cancersupporting
confidence: 69%
“…Spontaneous breast cancer development is delayed in both strains and to a similar extent in double‐deficient mice, indicating that PAR2 and downstream TF cytoplasmic domain phosphorylation cooperate in cancer progression, consistent with human pathology data in breast cancer . TF‐FVIIa‐PAR2 signaling has also been linked to human hepatocellular carcinoma (HCC) progression independent of downstream coagulation . In addition, TF ΔCT and PAR2‐deficient mice were similarly protected from carbon tetrachloride (CCl 4 ) damage leading to hepatic fibrosis involving transforming growth factor (TGF) β and macrophage activation.…”
Section: Tf‐par2 Signaling In Inflammatory Diseases and Cancersupporting
confidence: 69%
“…While IGFR cross-activation protects tumor cells from apoptosis through activation of the PI-3 kinase pathway, this pathway may participate in PI-3 kinase-Akt signaling dependent weight gain regulation by TF-FVIIa signaling (64). Cancer cell signaling of the TF-FVIIa-FXa coagulation initiation complex induces PI-3 kinase-mTOR signaling (65), which may be related to the finding that autophagy is suppressed by TF-PAR2 signaling in hepatocellular carcinoma (66). In addition to growth factor transactivation, TF-FVIIa influences tyrosine receptor signaling by direct proteolysis of the ephrin tyrosine kinase receptors B2 and A2 (67).…”
Section: Tf Signaling In Tumorcells and Angiogenesismentioning
confidence: 99%
“…Studies that target the TF/FVIIa signaling pathway with specific inhibitor or RNA interference provide a logical path for the development of potential therapeutics [44,45]. In our clinical observations in HCC, we were the first to demonstrate that the expressions of FVII and PAR2 were inversely correlated with the amount of autophagic effector proteins LC3A/B-II [46]. We have also demonstrated that the treatment with recombinant TF (rTF), rFVII, or PAR2 agonist decreased expression of LC3A/B-II protein in cultured Hep3B cells suggesting a crucial impact of the TF/FVII/PAR2 coagulation pathway on tumor malignancy under certain circumstances.…”
Section: Mtor Interconnects Coagulation Cascade and Autophagy In Hcc mentioning
confidence: 83%